Hypoxia in the Northern Gulf of Mexico - Dale, Virginia H.; Wright, Donelson; Kling, Catherine L.; Boynton, Walter; Meyer, Judith L.; Mankin, Kyle.; Sanders, James; Opaluch, James; Conley, Daniel J.; Stallworth, Holly; Crumpton, William; Paerl, Hans.; et al. (New York, NY : Springer New York, 2010)
Hypoxia in the Northern Gulf of Mexico is based on an extensive review conducted by the Hypoxia Advisory Panel of the Science Advisory Board for the Environmental Protection Agency, which was chaired by the editor. The book examines scientific advances that, since 2000, have increased understanding of hypoxia in the Gulf. It discusses characterization of its cause, characterization of its nutrient fate, transport, and sources, and the scientific basis for goals and management options. Using available data, including models, model results, and uncertainty, the advisory team addresses the strengths and limitations of managing the Gulf hypoxia problem. This book will be of interest to specialists in the fields of environmental sciences, social sciences, economics, landscape architecture, planning, and communication of risks. Virginia Dale is a Corporate Fellow in the Environmental Sciences Division at Oak Ridge National Laboratory. She is also an adjunct faculty member in the Department of Ecology and Evolutionary Biology at the University of Tennessee.
Table of Figures -- List of Tables -- Glossary of Terms -- List of Acronyms -- Conversion Factors and Abbreviations -- Executive Summary -- 1. Introduction -- 2. Characterization of Hypoxia -- 3. Nutrient Fate, Transport, and Sources -- 4. Scientific Basis for Goals and Management Options -- 5. Summary of Findings and Recommendations. References -- Appendices: A. Appendix A: Studies on the Effects of Hypoxia on Living Resources -- B. Appendix B: Flow diagrams and Mass Balance of Nutrients -- C. Appendix C: USEPA$1 (Bs Guidance on Nutrient Criteria -- D. Appendix D: Calculation of Point Source Inputs of N and P. E. Appendix E: Animal Production Systems.s
Keywords: Environmental sciences; Aquatic biology; Environmental law; Environmental management; Environmental pollution; Environment; Environmental Management; Freshwater & Marine Ecology; Environmental Monitoring/Analysis.; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Environment, general; Environmental Law/Policy/Ecojustice.